Mentorship for Teacher Induction. The Analysis of the Training Needs of the Beginning Teachers - Adrian Barbaroș; Mușata Bocoș (Babes-Bolyai University, 2023)
Mentorship in education plays a crucial role in facilitating the smooth integration of beginning teachers into the Romanian education system. Specifically designed for beginning teachers, this form of mentorship focuses on addressing their training needs through specific goals and implementation strategies. This study aims to identify the training needs of primary school beginning teachers across eight counties in Romania, including the municipality of Bucharest. The goal is to propose improvement measures to maximize the effectiveness of the mentorship program in which beginning teachers participate. The research methodology employed an online survey-based questionnaire administered in June 2023. Throughout the study, the authors shed light on various training needs relating to the teaching competencies of beginning teachers, including self-analysis of teaching activities, teaching methods, and satisfaction levels regarding the mentorship program. The findings highlight the diverse training needs of primary school beginning teachers from Romania and emphasize the importance of a coherent implementation of the mentoring programmes to address these needs effectively. This paper serves as a guiding resource for the development of mentorship and training programmes, as well as education policies aimed at enhancing the integration of beginning teachers into the Romanian education system.